Evaluation of Financial Feasibility of Egg-Laying Chicken Farming Business at CV “X”, South Lampung, Indonesia - Annisa Fitri; Deby Ananda Difah; Annisa Alifa Ramadhani; Dita Pratiwi (Indonesian Journal of Sustainable Agriculture and Environmental Sciences (IJSAES), 2025)
Background: Financial feasibility analysis enables entrepreneurs to get a clear picture of the potential profits that can be obtained, the time required for capital returns, and the strategies that must be adopted to face market challenges. Aim: The purpose of this research is to evaluate the economic feasibility of layer chicken farming at CV Rachmadi in Karang Sari Village, Jati Agung District, South Lampung. Methods: Primary and secondary data related to the farm's operations were collected in this study using qualitative and quantitative descriptive approaches. Primary data was obtained through direct observation and interviews with the owner and manager of the business. Secondary data was gathered from relevant literature and financial reports. The focus of the financial analysis is on costs, revenues, and profit projections. This analysis was conducted using methods such as net present value (NPV), Net B/C ratio, and internal rate of return (IRR). Results: The results of the study indicate a positive Net Present Value (NPV) of IDR 1,629,571,539.11, a B/C ratio (Net B/C) of 3.53, and an IRR of 47%, demonstrating that this business is financially feasible and profitable. Conclusion: These findings suggest that investing in this farm has good potential for long-term profit.